Finite element model for analysis of vibration damping characteristics of isotropic surface structures. (2022) - Pai, Anand; Kini, Chandrakant R.; Satish Shenoy, B.
Abstract: In this paper, a finite element (FE) model was developed to predict the vibration response of isotropic beams, involving several modes of resonance. The cantilever beam model was employed in the FE model in line with Timoshenko's bending theory. The FE analysis has been carried out using the modal analysis and harmonic analysis tools of Ansys R19.0. The FE model was subjected to a grid independence study to minimize the computational time without sacrificing accuracy. The resonant frequencies were utilized to compute the damping modulus of the material for both the FE and experimental results. The frequency response functions from the finite element analysis were compared with the experimental results of the cantilever beam subjected to impulse hammer excitation. Aluminium alloy AA6061-T6 was taken up as the homogeneous and isotropic beam material for both the experimental and the FE model. The effect of the magnitude and location of the excitation load, the geometry of the FE model on the vibration response was analyzed in detail. The FE model validation with the experimental results shows that the FE model is effective in predicting the damping response of any isotropic material.